A Comparison of Worldwide Fuels and their Effects on Combustion under Constant Volume Vessel Conditions - Vogel, Thomas; Rieß, Sebastian; Wensing, Michael (SAE Technical Papers, 2015)
Worldwide diesel fuels differ in their composition and therefore in thermo-physical properties. Some of these properties are known to have little effect on the combustion process. Others, like the cetane number, have dramatic influence on the combustion formation and thus on the heat release rate and more important the formation of soot and NOx. In an experiment series various commercially available fuel types, like EN 590 [1], ASTM D975 [2] and JIS K 2204 [3], have been compared to alternative diesel fuels such as FAME, GtL and premium diesel fuel with increased cetane number. A specially designed research injector was used in order to provide full optical access to one single fuel jet injected and combusted in a constant volume vessel. First, the liquid fuel phase propagation has been investigated by means of Mie-scattering and the liquid penetration depth and the spray cone angle have been evaluated. Here, the fuels with a higher amount of low volatile components, such as high alkanes, show increased liquid penetration depth. The focus in this measurement series is set on the ignition and combustion behavior. A set of two cameras has been applied to investigate the integral flame signal, dominated by the black body radiation, and the chemical luminescence of both, the OH∗ and CH∗ radical. To acquire these combustion radicals, band pass filters were used. The combustion behavior of the different fuels differs strongly, not only in ignition delay, but also in the combustion propagation, which is in indicator for the heat release rate. It was not always possible to build a link between the ignition delay and the cetane number. Especially the FAME-diesel fuels show a shortened ignition delay but a lower maximum heat release rate. High cetane number fuels show a high gradient in heat release rate.
Created from Fastlane, Scopus look-up